The complete chloroplast genome of Fargesia angustissima T. P. Yi: a panda dietary bamboo species - Hao Wu; Xue Li; Xianglei Xu; Yingjian Zhang; Tao Su (Mitochondrial DNA. Part B. Resources, 2023)
AbstractFargesia angustissima T. P. Yi, categorized into Arundinarieae (Poaceae: Bambusoideae), is a critical species endemic to Minshan Mountain, China. F. angustissima provides shelter and food sources for the giant panda and other endangered animals (e.g. red panda and snub-nosed monkey). This study assembled the complete chloroplast (cp) genome of F. angustissima using the high-throughput sequencing technique. The total cp length was 139,706 bp, containing 130 annotated genes with predicted GC content at 38.87%. The cp genome comprises two single-copy (LSC and SSC) regions, harboring 83,282 bp and 12,830 bp, respectively. The SSC regions were located between two inverted repeats (IR) regions (21,797 bp). Reconstruction of the phylogenetic tree illustrated that F. angustissima clustered F. canaliculata in Fargesia II. The study provides theoretical clues to explore the geographical distribution and species-level identification of the Fargesia genus.